DSCAMs: restoring balance to developmental forces - Garrett, Andrew M.; Burgess, Robert W.; Tadenev, Abigail L. (Frontiers in Molecular Neuroscience, 2012)
Many of the models of neurodevelopmental processes such as cell migration, axon outgrowth, and dendrite arborization involve cell adhesion and chemoattraction as critical physical or mechanical aspects of the mechanism. However, the prevention of adhesion or attraction is under-appreciated as a necessary, active process that balances these forces, insuring that the correct cells are present and adhering in the correct place at the correct time. The phenomenon of not adhering is often viewed as the passive alternative to adhesion, and in some cases this may be true. However, it is becoming increasingly clear that active signaling pathways are involved in preventing adhesion. These provide a balancing force during development that prevents overly exuberant adhesion, which would otherwise disrupt normal cellular and tissue morphogenesis. The strength of chemoattractive signals may be similarly modulated. Recent studies, described here, suggest that DSCAM, and closely related proteins such as DSCAML1, may play an important developmental role as such balancers in multiple systems.